Using the theory of planned behaviour to understand the adoption of vegetarianism among females in Saudi Arabia - Areej Ali Alkhaldy (Frontiers in Public Health)
BackgroundThe adoption of vegetarian diets is increasing worldwide, including among females in Saudi Arabia. This increase has not yet been explained. The present study explores the factors influencing the intention to follow a vegetarian diet among Saudi women using the theory of planned behavior (TPB) framework.Materials and methodsAn online self-administered questionnaire was distributed between July 2023 and January 2024. A total of 998 Saudi females participated, including both vegetarians (n = 417, 41.8%) and non-vegetarians (n = 581, 58.2%), who answered questions relating to their sociodemographic characteristics, awareness and perceived understanding of vegetarian diets, awareness of and adherence to dietary guidelines, dietary habits, and TPB predictors. Multivariable linear regression was used with dietary guideline awareness, body mass index, self-rated perceived weight, socioeconomic status index, and the TPB constructs as predictors to explain the intention to follow a vegetarian diet (outcome).ResultsAttitude (standardized β-coefficient = 0.29, p < 0.001), subjective norms (standardized β-coefficient = 0.10, p < 0.001), and perceived behavioral control (standardized β-coefficient = 0.08, p = 0.03) were significantly and positively associated with the intention to follow a vegetarian diet. However, dietary guideline awareness did not significantly influence the intention (standardized β-coefficient = −0.04, p = 0.1). Socioeconomic status index was negatively correlated with the intention to adopt a vegetarian diet (standardized β-coefficient = −0.073, p = 0.018). Body mass index showed no significant correlation with vegetarian diet intention (standardized β-coefficient = −0.05, p = 0.091).ConclusionTPB constructs (attitude, subjective norms, and perceived behavioral control) and socioeconomic status influence the intention to adopt a vegetarian diet, although awareness of dietary guidelines and body mass index do not.